Studies to determine the structure and function of Trk - K+ translocating system - Kale, Deepika Uttam (Jihočeská univerzita, 2020)
This thesis is focused on the functional and structural analysis of potassium translocation proteins (Trk) in the plasma membrane of yeast (S. cerevisiae and Pichia pastoris). In S. cerevisiae, Trk1 and Trk2 are the sole specific potassium uptake systems and required for growth in potassium limiting conditions. P. pastoris has only one Trk protein PpTrk, which had not yet been functionally analysed. All Trk proteins possess a huge cytosolic part of unknown role, the "long hydrophilic loop" (LHL). In order to investigate the role of LHL, functional studies were performed. Comparative functional analysis of Trk1 from S. cerevisiae and Trk from P. pastoris (PpTrk) revealed differences in the selectivity for monovalent cations. Furthermore, as a first step towards structure elucidation by X-ray diffraction crystallography, production of Trk proteins and parts of Trk proteins was attempted using different expression systems (E. coli, S. cerevisiae and P. pastoris).
Studies to determine the structure and function of Trk - K+ translocating system